(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The youth of the country especially college students can serve as a readily available pool of voluntary blood donors and help tide away some of the scarcity of blood and blood products. This study was conducted to determine the Knowledge, attitude and practice (KAP) regarding Voluntary Blood Donation among medical undergraduate studentsand to assess the factors which can lead to a subsequent increase in the same. Method: A cross-sectional descriptive study was conducted amongst 500 undergraduate medical students studying at Government Medical College, Patiala, Punjab using a structured, self-administered questionnaire regarding KAP. Results: The mean age of the 500 participating students was 20.46 years with a standard deviation of 1.5 of which 55.2% were females.71.2% and 61.4% students had correct knowledge regarding interval between blood donation for males and females respectively but the knowledge regarding common causes of deferral was less. Posters and pamphlets were the most common sources of information regarding blood donation.92.6% students had a good attitude towards blood donation. 127 (25.4%) students had donated blood previously and 17 (3.4%) of them had donated blood more than once in a year. Conclusion: The students had a fair knowledge about VBD and the majority had a favourable attitude towards it. Steps should be taken to increase the awareness regarding VBD since early sensitisation towards its importance can motivate students to become voluntary blood donors, making them major contributors to the blood donor pool throughout their adulthood and help in overcoming blood shortage in the country.